Hubungan Antara Keselamatan dan Kesehatan Kerja (K3) dan Motivasi Kerja dengan Kepuasan Kerja Karyawan dada Suku Dinas Penanggulangan Kebakaran dan Penyelamaan Kota Administrasi Jakarta Selatan - Syahyuni, Dedy (www.bsi.ac.id, 2019)
Abstract – In many organization, work satisfaction of employees is one of the things that began to be considered in addition to employee performance. Although not all organizations agree but many research has been conducted and now we beginning to have a lot of experts who agree that there is a link between performance improvement and high employee satisfaction rate. Therefore, same organization need to consider how to improve employee work satisfaction. In an organization that engaged in the service, the satisfaction of employees can not be underestimated because employees who are not satisfied with the work and or organization will look bad in the delivery of services to customers or their stake holder, It is very unfortunate because in many place the service is given then the service should look very well. So this job satisfaction becomes more important in the organization especially in Suku Dinas Penangulangan Kebakaran Dan Penyelamatan Kota Administrasi Jakarta Selatan, An organization that not only gives service but give service of a rescue of wealth and soul of a citizen. If the employees are not satisfied with the work and or with organization, then the rescue service will be not maximal. This is important because all employees or members of the fire department are required to work perfectly in every asigment because they always faced with danger. Therefore, this article wants to discuss how the occupational safety and health that employees get is in accordance with what they expect in the daily life of their duties and how they are motivated in the work and whether these two things affect job satisfaction. Key Word: occupational safety and health, Work Motivation dan Job Satisfaction